Expansão urbana e qualidade ambiental : uma análise da cobertura vegetal em Rondonópolis - MT entre os anos de 2006 e 2015 - Duarte, Taise Ernestina Prestes Nogueira (2016)
The objective of this dissertation was to analyze the urban environmental quality in Rondonópolis in the face of the urban expansion between 2006 and 2015, with plant cover being the main parameter of environmental quality. This analysis included three steps: Analysis of the urban expansion, mapping of the vegetation cover and survey of the aspects involved in the characteristics of the urban vegetation cover in Rondonópolis – MT, Brazil. For the mapping of the urban vegetation cover in Rondonópolis, the NDVI calculation was used as the main resource, according to the methodology suggested by Sá et al (2010). From the development of the present study, it could be considered that the urban expansion in Rondonópolis reveals clear signs of a process of urbanization dictated by the interests of capital. Vegetation cover is relatively low in most of the neighborhoods surveyed, and there have been significant losses in the last ten years. Among the aspects involved in the characteristics of the urban vegetation cover in Rondonópolis were: natural aspects, time of urbanization, environmental injustice and urban legislation. In this way, it was verified that natural aspects such as altitude and the presence of riparian forests influenced in a greater amount of vegetal cover in some places. It was verified that the time of urbanization was proportional to the amount of vegetal cover present in the neighborhood, as well as, the differentiation in the access to the vegetal cover between the social classes was verified, where the social classes of greater income obtained quantity of superior vegetal cover In almost all the neighborhoods surveyed. With regard to urban legislation related to vegetation cover, it was found that the fragility of municipal legislation is responsible for the low diversity of vegetation cover found, as well as the lack of actions aimed at valorizing vegetation cover as an essential element in urban spaces. Reflected in the urban landscape of Rondonópolis. Based on the data collected, it was possible to verify that the Master Plan (2006/2015) was not effective in providing environmental quality to all residents during its period of validity, and that environmental quality worsened during this period and its Access was segregating.